Knowledge and Attitude on The Use of Nano Particle Based Herbal Mouthwash Among Dental Students – A Survey - SELVAMARY, V. NANCY; T, LAKSHMI.; GIRIJA, SMILINE (The journal of contemporary issues in business and government, 2021)
Many investigations have pointed out widespread use of the herbal based nano system in various domains of dentistry such as prevention, prognosis, care, tissue regeneration and restoration. Nano material in mouthwashes to improve oral health performance. The main aim of the research to assess the knowledge and attitude on the use of nanoparticle based herbal mouthwash among dental students. A questionnaire based survey was conducted online among dental students regarding their knowledge and awareness about the mouth washing habits and awareness about nano based herbal mouthwashes. Total students participated :100. Total questions asked :13. Spss analysis with chi-square test is done for analysis. From the results it's evident that among the total (100) students participating in the survey 51.52% were female, 48.48% male. 83.84% of students were using mouthwash daily. 86.87% students prefer herbal mouthwash, 56.57% students were aware about nanoparticles, 79.80% students are aware about the purpose of using mouthwash, 18.18% students used nano particle mouthwash. 54.55% of students didn’t have dental problems. 56.57% of students, dentists motivate them to use mouthwash. 84.85% of students know that mouthwash has greater ability to reduce bacteria in the mouth, 78.79% of students know the usage of mouthwash in reducing dental caries. Among all students, 57.58% are aware about nano based herbal mouthwashes.This study concluded that more of them are aware about nanoparticle based herbal mouthwashes.